Wild Parties in Prehistoric Greece - Dalby, Andrew (Petits Propos Culinaires, 2014)
The article summarizes for lay readers some archaelogical finds at the Greek site of Makrygialos (inhabited from about 5300 to 4950 bc) which indicated feasting on a scale not commensurate with the size of the settlement and discusses other archaeological research about Mycenaen feasting.